(untitled) (Discussion Papers, 2012)
Continuation of co-operation between researchers, aiming to expand the XVth Polish-Hungarian Geographical Seminar, and to support the initiative of Warsaw Regional Forums, the Centre for Regional Studies, Hungarian Academy of Sciences and the Geographical Research Institute, Hungarian Academy of Sciences organised the East-Central European Regional Seminar 2006. The general topics of the seminar were the spatial, regional and local issues and conflicts of East-Central European regions, analysis and comparison of regional and local processes. The region is considered to be a spatial unit serving the sustainable growth of the economy and the modernisation of the spatial structure, with independent financial resources, fulfilling autonomous development policy and equipped with local government rights. The region, if defined as a framework for regional research, is not capable of organising the space-forming powers of the 21st century without the competencies, institutions and tools. Regions in the new member-states are necessary, since European regional development clearly proves that a sub-national level comprising approximately 1-2 million inhabitants regulated on the basis of self-government concepts (as a result of the region’s economic capacity and structural abilities) is considered to be the optimal spatial framework for the realisation of regional development policy, the appropriate field for the operation of post-industrial spatial organisation forces, the most appropriate size of spatial unit to build a modern infrastructure and the professional organising-planning-executing institution of regional policy, the main factor in the decision-making system of the European Union’s Regional and Cohesion policy.